P854 Interspecies chimeras: a tool to identify chlamydial virulence factors. (14th July 2019) - Fernandez, Mark; Suchland, Robert; Hybiske, Kevin
Abstract : Background: Chlamydia trachomatis is an obligate intracellular bacterium and is the most common notifiable infection in the United States. It spends its entire developmental cycle in a membrane bound cytosolic vacuole termed the inclusion, which protects it from otherwise deleterious host innate immune responses. Interferon gamma (IFNγ) plays a critical role in the clearance of Chlamydia in vitro and in vivo, at least in part by inducing cell-autonomous immunity in infected epithelial cells. Chlamydia muridarum, a rodent pathogen with high genomic synteny to C. trachomatis, is completely susceptible to human cell-autonomous immune responses in vitro . In contrast, C. trachomatis is highly resistant to these IFNγ-induced responses. In published coinfection experiments, inclusions coinhabited by these species are resistant to recognition by cell-autonomous immunity, suggesting that C. trachomatis has evolved active mechanisms to evade recognition by host cytosolic immune surveillance. These mechanisms are completely unknown. Methods: To identify chlamydial genes that may be involved, we have taken advantage of a previously generated library of interspecies chimeras, each of which has a genome that is predominantly C. trachomatis serovar L2 with discrete regions of C. muridarum genes recombined in (range = 12–113 recombined genes in each individual chimera). We have used these chimeras in an initial screen looking for ubiquitin recruitment to inclusion membranes—an established marker of cell-autonomous immunity recognition. Results: We have identified four chimeras that are ubiquitinated following IFNy stimulation. These four have zones of recombination overlapping with one another, providing us with 11 candidate genes. Conclusion: This outcome highlights the utility of our chimera library, especially when used to identify genetic factors underlying phenotypes for which C. trachomatis and C. murdarum are disparate. Future characterization of the candidate genes in this screen will identify chlamydial virulence factors that aid in immune evasion of IFNγ-induced host responses, and may inform design of future vaccines. Disclosure: No significant relationships.